Concurrent TMS-EEG to reveal the neuroplastic changes in the prefrontal and insular cortices in the analgesic effects of DLPFC-rTMS. (20th January 2022) - Ye, Yang; Wang, Jinghua; Che, Xianwei
Abstract: The dorsolateral prefrontal cortex (DLPFC) is an important target for repetitive transcranial magnetic stimulation (rTMS) to reduce pain. However, the analgesic efficacy of DLPFC-rTMS needs to be optimized, in which the mechanisms of action remain unclear. Concurrent TMS and electroencephalogram (TMS-EEG) is able to evaluate neuroplastic changes beyond the motor cortex. Using TMS-EEG, this study was designed to investigate the local and distributed neuroplastic changes associated with DLPFC analgesia. Thirty-four healthy adults received DLPFC or sham stimulation in a randomized, crossover design. In each session, participants underwent cold pain and TMS-EEG assessment both before and after 10-Hz rTMS. We provide novel findings that DLPFC analgesia is associated with a smaller N120 amplitude in the contralateral prefrontal cortex as well as with a larger N120 peak in the ipsilateral insular cortex. Furthermore, there was a strong negative correlation between N120 changes of these two regions whereby the amplitude changes of this dyad were associated with increased pain threshold. In addition, DLPFC stimulation enhanced coherence between the prefrontal and somatosensory cortices oscillating in the gamma frequency. Overall, our data present novel evidence on local and distributed neuroplastic changes associated with DLPFC analgesia.